Primary splenic echinococcosis with brief review of the literature: About a case - Dávila-Hernández, Carlos A. (2023)
Introduction: Splenic echinococcosis is a zoonotic disease accidentally acquired by humans as an intermediate host. Case report: a 26-year-old female patient with abdominal pain located in the left hypochondrium, moderate intensity, calmed with intravenous antispasmodics; a history of long-standing abdominal pain and from the Huancavelica region, Peru, 6 years ago. On clinical examination of the abdomen: hydro-air sounds; present, symmetrical, soft, depressible, painful on palpation in the left hypochondrium, impression of splenomegaly, preserved tympany; the ultrasound mentions a hydatid cyst at the level of the spleen – Gharbi IV; Contrast-enhanced abdominal and pelvic tomography shows a spleen with a heterogeneous cystic lesion, with a partially calcified wall and areas of fatty density that extend to the gastrosplenic ligament, with a diameter of 73 mm x 54 mm; concluding extrahepatic echinococcosis (splenic echinococcosis), performing total splenectomy. Conclusion: rare disease, even in endemic areas, which poses challenges for its diagnosis and treatment.